Investigating the Characteristics of Tramadol-induced Seizures: A Cross-sectional Study - Soroosh, Davood; Foroughian, Mahdi; Zarmehri, Bahram (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: According to statistics, tramadol intoxication is one of the most common drug poisoning cases in Iran. Because seizure is one of the severe and dangerous side effects of tramadol, the present study aimed to investigate the characteristics of tramadol-induced seizures. Methods: In this cross-sectional descriptive study, all patients who referred to the emergency departments due to the tramadol-induced seizures were examined by the census method. The patients’ data were collected with a checklist. Then, the data were analyzed with descriptive and inferential statistical tests in SPSS v. 23 and at a significant level of P<0.05. Results: In this study, 350 patients (52.9% male, and 47.1% female) were examined. The Mean±SD dose consumed was 1171.4±802.77 mg. The minimum dose that caused the seizure was 200 mg, and the average dose consumed of tramadol was different in patients who had one, two, or three seizures outside the hospital (P=0.002). The consumed average dose of tramadol was 1144.5 mg, 2017.7 mg, and 511.1 mg for patients who had one, two, or three seizure(s), respectively. There was a significant relationship between dose consumed and the number of seizures (P=0.001). The study showed that patients who had a one-time seizure, have experienced this condition outside the hospital. There was a significant relationship between the number of seizures and the location of the seizure (outside or inside the hospital) (P=0.001). Conclusion: The results showed no significant relationship between consumed dose and location of the seizure. The number of seizures is not dependent on the consumed dose. It means that increasing the consumed dose, the number of seizures does not increase, and there is no significant relationship between the amount of dose consumed and the number of seizures.